Analysis of Vibration Transmission Path in Packaging System and Design of Teaching Experiment - Gong, Meilin; Lin, Cong (Shock and Vibration, 2024)
It is essential for realizing the most suitable product buffer packaging design to quantify the vibration transmission characteristics of the product packaging system. The experiment system for the vibration transmission path of protective packaging is designed in this paper. The practical system is used to analyze the vibration transfer path of the product packaging system and identify the critical transfer path. The concepts of the cushions’ contribution rate and the cushions’ weighted contribution rate are introduced. The product cushioning based on the weighted equal contribution rate of the cushions is proposed. It has been verified by experiments that the system can accurately identify the transfer path with the weighted contribution rate of the cushions as a reference for the design of product buffer packaging, which improves the utilization rate of buffer packaging materials and reduces the cost of packaging materials. The weighted equal contribution rates of buffer pads 1, 2, 3, and 4 are 40%, 27%, 22%, and 11%, respectively. For the needs of experiment teaching, the teaching content based on the protective packaging transfer path testing system is designed, which provides a reference for the practical education of the packaging specialty.